If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2(x + -1) = 8x + 15 + -3x Reorder the terms: 6x + -2(-1 + x) = 8x + 15 + -3x 6x + (-1 * -2 + x * -2) = 8x + 15 + -3x 6x + (2 + -2x) = 8x + 15 + -3x Reorder the terms: 2 + 6x + -2x = 8x + 15 + -3x Combine like terms: 6x + -2x = 4x 2 + 4x = 8x + 15 + -3x Reorder the terms: 2 + 4x = 15 + 8x + -3x Combine like terms: 8x + -3x = 5x 2 + 4x = 15 + 5x Solving 2 + 4x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + 4x + -5x = 15 + 5x + -5x Combine like terms: 4x + -5x = -1x 2 + -1x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -1x = 15 + 0 2 + -1x = 15 Add '-2' to each side of the equation. 2 + -2 + -1x = 15 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 15 + -2 -1x = 15 + -2 Combine like terms: 15 + -2 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| 7x+37=32 | | Y=x^2+3x-22 | | 3(-12z-5)+10=12(-3z+5)-61 | | p-88=72/5(88-7) | | 7.5+0.5x+3/4x | | 7p+22p+3=0 | | p-17/1=72/5(-7) | | p-17/2=72/5(-7) | | 10x+9=66 | | p-17/5=72/5(-7) | | p-17=72/5(-7) | | (5x^3)-4x=76 | | 2x^2+21x-36=0 | | y=-1/2*4-4 | | 4x^2+16x=34x | | p-18=72/5(20-7) | | y=12x-3 | | y=-1/2(-0.5)-4 | | y=-1/2(0.5)-4 | | p-25=67/8(18-6) | | 3q^2=-27q^4+51q^3-9q^2 | | 3(x/2-1)=5x-3 | | p-18=72/5(18-7) | | s^3+7s^2+25s+39=0 | | p-18=23/3(18-6) | | x+(6/4.3)=y | | 4x^3-12x^2+12x+3=0 | | -6*0-4y=24 | | 9x^2-20x+50=0 | | ln(x)=ln(x+4)-ln(3) | | 35y^3-220y^2-175y=0 | | -6x-4*0=24 |